Press imprint smear : um método simples, rápido e de baixo custo no diagnóstico de Leishmaniose cutânea - Praciano, Claudênia Costa (2014)
The cutaneous leishmaniasis (CL) is the most common form of leishmaniasis, with 1 million new cases per year. Presents a broad clinical spectrum, which may be confused with other diseases that affect the skin. Thus, it is of fundamental importance to rapid and accurate diagnosis of the disease. Parasitological diagnosis is the most used test in laboratory routine, however direct examination generally has low sensitivity. As a result, it becomes necessary to find alternative techniques for the diagnosis of leishmaniasis. This study compared the test press imprint smear with histological examination and immunohistochemistry, for the direct diagnosis of leishmaniasis. Patients with clinical suspicion of LC underwent a sampling from two samples of biopsies from the edge of the lesions, with a punch of 3 mm for the tests: press imprint smear, histological examination and immunohistochemistry. The latter was considered the gold standard test. The press imprint smear consisted in crushing the biopsy fragment between two glass plates under pressure so that the extract (juice) tissue spreads on the surface of the two blades. The smears were stained with Giemsa for the detection of amastigotes. Another fragment was fixed in 10% formalin. From this sample, a blade was used in histology, stained with hematoxylin-eosin, and one for the immunohistochemical test. In total, 78 patients were included with clinical and epidemiological diagnosis of LC. The press imprint smear technique and histologic examination were conducted on the sample of all patients. However, immunohistochemistry was performed in only 73 samples. Seventy-two (98,6%) were positive for leishmania in immunohistochemistry, with sensitivity of 98,6%; the press imprint smear was positive in 48 patients (61,5%), with sensitivity of 58,3%. In the histological examination were identified amastigotes in 35 patients (44,9%), with sensitivity of 45,8%. The press imprint smear was more sensitive than histological examination for the diagnosis of cutaneous leishmaniasis. In addition, a technique is inexpensive and easy to perform.